(untitled) (International Seven Journal of Health Research, 2023)
The proportion of elderly people has been increasing in recent years, and with it the related public health problems. Intentional self-inflicted injuries are an important public health problem, even among this section of the population. The aim of this study was to describe the panorama of self-inflicted injuries in the elderly population of the southeast region between 2011 and 2015. It was concluded that self-inflicted injuries in the elderly ranked 6th among external causes of morbidity and mortality between 2011 and 2015 in the southeast region, demonstrating the relevance of the issue in this part of the population. Suicide among the over-60s occurs more frequently in men. It is necessary to identify these patients and what leads them to idealize the suicidal act so that we can address factors that improve their mental health in order to prevent this event.